El “intelectual colectivo” y la construcción de una nueva hegemonía (2020)
This article will address the contributions made by Gramsci in the construction of the figure of the intellectual. To do this, the distinctive dyes of Marxist historical determinism will be characterized, and then focus on the Gramscian thought. From there we will expressly focus on the arguments deployed by Gramsci by procuring an active role to the figure of the intellectual, as a collective intellectual that is becoming embodied in the revolutionary party of the working class. In this way, we will propose that this disposition of the collective intellectual is linked to the problems of social life in the search to unify theory and praxis, and seeks to create a new hegemony, since it admits the indeterminacy of history according to laws.